2016
DOI: 10.1063/1.4972072
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of plasma sheath with nonextensively distributed two-temperature electrons and isothermal ions

Abstract: This paper presents the behavior of plasma profiles of a sheath in unmagnetized collisionless plasma in the presence of nonextensively distributed two-temperature electrons and isothermal ions. A theoretical model is developed where isothermal ions are described by the conventional hydrodynamic equations along with the effect of electron nonextensivity described by q-distribution function. The plasma sheath parameters like Bohm velocity, potential, and density profiles in the presence of nonextensively distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…A homogeneous, unmagnetized three‐component plasma is considered, which consists of cold inertial fluid ions, hot nonextensive electrons, and cool Maxwellian electrons. Under Tsallis nonextensive formalism, the velocity distribution function in one dimension is expressed by fe()v=Cq1q1mev22TnormaleitaliceϕTe1q1, where q represents strength of nonextensivity. m e , e , T e , and v are mass, magnitude of charge, temperature, and thermal velocity of electrons, respectively.…”
Section: Theoretical Model and Basic Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A homogeneous, unmagnetized three‐component plasma is considered, which consists of cold inertial fluid ions, hot nonextensive electrons, and cool Maxwellian electrons. Under Tsallis nonextensive formalism, the velocity distribution function in one dimension is expressed by fe()v=Cq1q1mev22TnormaleitaliceϕTe1q1, where q represents strength of nonextensivity. m e , e , T e , and v are mass, magnitude of charge, temperature, and thermal velocity of electrons, respectively.…”
Section: Theoretical Model and Basic Equationsmentioning
confidence: 99%
“…Finally, for our plasma model, the hot q ‐nonextensive electron density is expressed as, nh=nnormalh01+q1italiceϕTnormalhq+12q1, …”
Section: Theoretical Model and Basic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the q-distribution has been considered equal to the κ-distributions in the space plasmas [19,22,[24][25][26][27][28][29][30][31].…”
Section: -----------------------------------------mentioning
confidence: 99%
“…[47][48][49][50][51] For example, Hatami [49] studied the sheath formation criterion in a collisional plasma consisting of non-extensively distributed electrons and thermal ions, and discussed the effect of non-extensive electrons on the behaviour of the density distribution of charged particles. Furthermore, the sheath in the presence of two-temperature q-non-extensive electrons [52][53][54] in the electronegative plasma [55] was investigated recently and it's shown that the presence of non-extensive electron strongly modifies the sheath structure. In their model, the investigations are limited to the plasma sheath without dust particles.…”
mentioning
confidence: 99%